Salivary cortisol as an indicator of adrenocortical function in healthy infants, using massage therapy - Fogaça, Monalisa de Cássia; Carvalho, Werther Brunow; Peres, Clóvis de Araújo; Lora, Mayra Ivanoff; Hayashi, Lilian Fukusima; Verreschi, Ieda Therezinha do Nascimento (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: The evaluation of adrenocortical function with the use of therapeu- tic massage has been little studied in Brazil. The purpose of this study was to evaluate the salivary cortisol levels before and after Shantala massage therapy on healthy infants. DESIGN AND SETTING: Prospective case series, in a public nursery, in São Paulo. METHODS: Saliva was obtained from 11 infants at the times of 8:00-9:00 a.m. and 4:00-5:00 p.m. in a nursery and 9:00-10:00 p.m. at home. They received a 15-minute therapeutic massage on two consecutive days, and saliva was collected before and after the massage. The procedure was repeated after a one week interval. Cortisol values (intra-assay < 5%; inter-assay < 10%) at different times of the day were compared by ANOVA. RESULTS: The mean cortisol values (nmol/l ± SD) on the first day were: morning (M) = 14.1 ± 5.7, afternoon (A) = 8.3 ± 2.7, night (N) = 3.3 ± ± 1.1; after two consecutive days of therapeutic massage: M = 22.3 ± 13.5, A = 13.4 ± 6.0, N = 5.8 ± 3.5; after a one-week interval: M = 15.8 ± 7.7, A = 14.3 ± 7.7, N = 3.4 ± 2.0. CONCLUSION: There was a modification in the salivary cortisol values following massage, thus reflecting possible adaptation of the hypotha- lamic-pituitary-adrenal axis.